A review of recreation requirements in U.S. juvenile justice facilities - León, Maria (Criminal justice policy review, 2020)
In the United States, the mission of the Office of Juvenile Justice and Delinquency Prevention includes the development and implementation of prevention and intervention programs. While many of these initiatives include recreation, there remains no standard for recreation programs. The purpose of this study was to review the written authorities for each state to identify the minimum requirements for recreation programming in juvenile justice facilities. Among other discoveries, we found that across all states, there is not a shared definition of recreation, only 70% of states have daily mandatory minimums requirements, only 44% of states require youth be given time outside, and only 56% of states include justifications for denying youth access to recreation. Implications for professionals and researchers are discussed, as well as suggestions for further inquiry and the integration of recreation into the treatment process.